2014
DOI: 10.1007/s10546-014-9931-5
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to the Third GEWEX Atmospheric Boundary Layer Study (GABLS3)

Abstract: The atmospheric boundary layer (ABL) plays a dominant role in the exchange of energy, water vapour, trace gases and momentum between the earth's surface and the overlying atmosphere. Consequently, the ABL is an important part of any numerical model in use for atmospheric and climate research, for operational weather forecasting, and for air-quality and wind-energy studies. For all these applications an overall representation is needed for boundary-layer turbulence and near-surface processes, as well as for ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…The aim of this investigation is to introduce a new approach for skill-testing CTMs regarding: (i) reproducing meteorological conditions, (ii) transporting and mixing primary emissions in the atmospheric boundary layer (ABL), and (iii) forming secondary gaseous and aerosol products. Since understanding of the physical processes associated with transport and mixing under fair-weather turbulent daytime conditions is more advanced than processes dominating near quiescent nocturnal conditions near the surface [12][13][14][15][16], model skill will also be dependent on atmospheric mixing state. Furthermore, the formation of secondary pollutants is also dependent on factors related to the atmospheric mixing state (e.g., mixing volume, temperature, sunlight intensity, humidity, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this investigation is to introduce a new approach for skill-testing CTMs regarding: (i) reproducing meteorological conditions, (ii) transporting and mixing primary emissions in the atmospheric boundary layer (ABL), and (iii) forming secondary gaseous and aerosol products. Since understanding of the physical processes associated with transport and mixing under fair-weather turbulent daytime conditions is more advanced than processes dominating near quiescent nocturnal conditions near the surface [12][13][14][15][16], model skill will also be dependent on atmospheric mixing state. Furthermore, the formation of secondary pollutants is also dependent on factors related to the atmospheric mixing state (e.g., mixing volume, temperature, sunlight intensity, humidity, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The challenges of the first two GABLS exercises inspired the setup of GABLS3, which deals with a real diurnal case with a strong nocturnal low-level jet (LLJ) at the Cabauw meteorological tower in the Netherlands (Baas et al, 2009;Holtslag, 2014;Basu et al, 2011;Bosveld et al, 2014a). Here, large-scale forcing is not constant throughout the diurnal cycle but depends on time and height.…”
Section: Introductionmentioning
confidence: 99%
“…Still, there is a quite significant variability depending on the PBL scheme and grid set‐up. These studies showed how the complexity of interpreting large‐scale forcing and the interaction with the surface made it difficult to compare models with observations …”
Section: Microscale Modelingmentioning
confidence: 99%